A facile approach to produce holey graphene and its application in supercapacitors. (January 2015) - Peng, You-Yu; Liu, Yih-Ming; Chang, Jeng-Kuei; Wu, Chia-Hung; Ger, Ming-Der; Pu, Nen-Wen; Chang, Chien-Liang
Abstract: We demonstrate a low-cost and simple method to prepare holey graphene nanosheets (HGNSs) by ultra-rapid heating during the process of thermal reduction/exfoliation of graphite oxide. The number density of the holes increased with the heating rate, and the size ranged between 10 and 250 nm. In addition, supercapacitors (SCs) using HGNSs as the electrode material were fabricated and their performances were evaluated. Compared to common graphene, HGNSs offered much higher capacitance values and better capability at high rates due to the much shorter cross-plane ion transport paths in the graphene stack through the large amount of holes on graphene sheets. The SC with HGNS electrodes exhibited an excellent high-rate capacitance of 170 F/g at 50 A/g in a 6 M KOH aqueous electrolyte. In the low-rate limit, the HGNS SC showed a very large specific capacitance of 350 F/g at 0.1 A/g.